A concept of cooling clothing for construction workers in Malaysia / Zulhilmi Mohd - Mohd, Zulhilmi (2018)
The construction industry is the one of the highest contributor towards economic growth in a country. The construction industry also acts as an indicator whether the nation is developing or stagnated. Every year all around the globe each nation has their own construction running whether it is a small project or mega money project. Hence, job opportunities are present and being offered to all people to get involved in construction industry. But, the construction industry is the high level of risk industry where the dangers exposure towards the workers are high. There are many accidents occurred annually and also many fatalities for examples are heat stroke and heat related illness accidents. Thus, heat exposure also considered as a threat to workers' safety. Research has shown a linkage between heat exposure to increased rate of unsafe behaviours. The purposes of this research were to tackle the issue and propose a new concept of clothing for construction workers. The principal method of this research is to ensure the comfortable of workers when working under a heat and to reduce the heat stress. By designing a cooling clothing, the workers will be more comfortable and can increase their productivity. Hence, it also can reduce the accidents occur related to heat illness.